The Network of Interactions Among Porcine Reproductive and Respiratory Syndrome Virus Non-structural Proteins - Nan, Hao; Lan, Jixun; Tian, Mengmeng; Dong, Shan; Tian, Jiao; Liu, Long; Xu, Xiaodong; Chen, Hongying (Frontiers in Microbiology, 2018)
The RNA synthesis of porcine reproductive and respiratory syndrome virus (PRRSV), a positive-strand RNA virus, is compartmentalized in virus-induced double-membrane vesicles where viral proteins and some cellular proteins assemble into replication and transcription complexes (RTCs). The viral replicase proteins are the major components of the RTCs but the physical associations among these nonstructural proteins (nsps) remain elusive. In this study, we investigated the potential interactions between PRRSV nsps by yeast two-hybrid (Y2H), bimolecular fluorescence complementation (BiFC) and pull-down assays. Our analyses revealed a complex network of interactions involving most of PRRSV nsps. Among them, nsp9 and nsp12 were identified as the hubs of the nsp interactome; transmembrane proteins nsp2 and nsp5 both interacted with nsp3, indicating that the three membrane-bound proteins might bind together to form the scaffold to support the association of RTCs with the intracellular membrane. The PRRSV nsp interactions identified in this study may provide valuable clues for future researches on the RTC formation and function.